Commercial Orchids - De, Lakshman Chandra (De Gruyter, 2015)
Orchids account for a large share of global floriculture trade both as cut flowers and as potted plants, and are estimated to comprise around 10% of international fresh cut flower trade. The average value of fresh cut orchids and buds trade during 2007-2012 was US$ 483 million. In 2012, there are more than 40 countries exporting orchids and 60 countries importing orchids around the world, with the total size of the global trade equaling US$ 504 million. In India, about 1350 species belonging to 186 genera represent approximately 5.98% of the world orchid flora and 6.83% of the flowering plants in India. The publication on "Commercial Orchids" is presented in 15 interesting chapters vividly highlighting the global orchid industry, bio-diversity, conservation and bio-piracy of genetic resources, morphological and molecular characterization of valuable species, breeding approaches for improved genotypes, production of quality planting materials, physiology of tropical and temperate orchids, climate change and its impact on orchid productivity, production technology of commercial epiphytic orchids for cut flower, production technology of commercial terrestrial orchids for cut flower, orchids for pot culture, hanging baskets and tree mounting, medicinal and aromatic orchids, post-harvest management of cut flowers of commercial orchids, value addition and marketing.